Depilatory double‐disc mouse model for evaluation of vesicant dermal injury pharmacotherapy countermeasures - Tomas L. Roldan; Shike Li; Jeffrey D. Laskin; Dayuan Gao; Patrick J. Sinko (Animal Models and Experimental Medicine, 2023)
Abstract Background Sulfur mustard (SM) is a chemical warfare vesicant that severely injures exposed eyes, lungs, and skin. Mechlorethamine hydrochloride (NM) is widely used as an SM surrogate. This study aimed to develop a depilatory double‐disc (DDD) NM skin burn model for investigating vesicant pharmacotherapy countermeasures. Methods Hair removal method (clipping only versus clipping followed by a depilatory), the effect of acetone in the vesicant administration vehicle, NM dose (0.5–20 μmol), vehicle volume (5–20 μl), and time course (0.5–21 days) were investigated using male and female CD‐1 mice. Edema, an indicator of burn response, was assessed by biopsy skin weight. The ideal NM dose to induce partial‐thickness burns was assessed by edema and histopathologic evaluation. The optimized DDD model was validated using an established reagent, NDH‐4338, a cyclooxygenase, inducible nitric oxide synthase, and acetylcholinesterase inhibitor prodrug. Results Clipping/depilatory resulted in a 5‐fold higher skin edematous response and was highly reproducible (18‐fold lower %CV) compared to clipping alone. Acetone did not affect edema formation. Peak edema occurred 24–48 h after NM administration using optimized dosing methods and volume. Ideal partial‐thickness burns were achieved with 5 μmol of NM and responded to treatment with NDH‐4338. No differences in burn edematous responses were observed between males and females. Conclusion A highly reproducible and sensitive partial‐thickness skin burn model was developed for assessing vesicant pharmacotherapy countermeasures. This model provides clinically relevant wound severity and eliminates the need for organic solvents that induce changes to the skin barrier function.